Pragmatic sociology, representations and politics. Device for a study on the right - Quiroga, Paula Inés (Mediaciones Sociales, 2024)
From pragmatic sociology we seek to contribute to the understanding of the social order. It is an approach that seeks to overcome determinisms and indeterminisms. We rely on contributions from framing; which is a theory and a methodology from which we investigate the significant practices of the Argentine right, studying their frameworks of meaning; and through tools that range from discourse and image analysis to sociology. We approach the concept of representations in a double register: in the symbolic, as sets of experiences, and in the field of politics, as an occupation instead of someone else. To think about this in practice, we carried out a preliminary study on the representations that the Cambiemos Alliance made in 2015 of its candidate for the province of Buenos Aires.
Keywords: pragmatism; sociology; interaction; role play; framing